Examination of deteriogenic biofilms on building facades with scanning electron microscopy = Badanie deteriogennych nalotów biologicznych na elewacjach budynków metodą elektronowej mikroskopii skaningowej - Piontek, Marlena; Lechów, Hanna; Paradowska, Ewa; Nycz, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Destruction of facades is a complex process in which technical material changes its properties, and which is caused by depositing biological agents. The examination of biofilms from building facades is difficult because sampling for tests may result in the damage to the structure of the facade's material. Also biological analysis of the material obtained from a biofilm is arduous.
Keywords: nalot biologiczny; elektronowa mikroskopia skaningowa; SEM; elewacje; biokorozja; biodeterioracja; biofilm; scanning electron microscope; facade; biocorrosion; biodeterioration